Orthodox Church History / Teacher's Manual (Apostoliki Diakonia of The Orthodox Church of Gree, 2002)
The Ancient World, The Israelites and the Chosen People of God, The Fulness of Time, The Church is Established, The Holy Apostles, Christianity Speads to the World, St. Paul's Missionary Journeys, The Church Develops, Christianity Spreads in Spite of Conflicts, Apostolic Fathers of the Church, The Persecutions (External Conflicts), The Church Grew and Expanded, The Triumh of the Church, The Creed of Faith, Development of the Orthodox Monasticism, Christianity Spreads to the Slavic Nations, The Separation of East and West, The Great Schism, Other Differences Between the Churches, Period of Crusades, The Orthodox Church and Scholasticism, Pillars of Orthodoxy: Monasticism and St. Gregory Palamas, Protestand Reformation, The Reformation Continues, English Reformation, General Conclusion on Protestantism, The Byzantine Empire Collapsed but Orthodoxy Prevailed, Appendix.